Reliability and validity of Yo-Yo tests in 9- to 16-year-old football players and matched non-sports active schoolboys - Póvoas, Susana C. A.; Castagna, Carlo; Soares, José M. C.; Silva, Pedro M. R.; Lopes, Mariana V. M. F.; Krustrup, Peter (European journal of sport science, 2016)
The purpose of this study was to examine the test-retest reliability and construct validity of three age-adapted Yo-Yo intermittent tests in football players aged 9-16 years (n = 70) and in age-matched non-sports active boys (n = 72). Within 7 days, each participant performed two repetitions of an age-related intensity-adapted Yo-Yo intermittent test, i.e. the Yo-Yo intermittent recovery level 1 children's test for 9- to 11-year-olds; the Yo-Yo intermittent endurance level 1 for 12- to 13-year-olds and the Yo-Yo intermittent endurance level 2 test for 14- to 16-year-olds. Peak heart rate (HR peak ) was determined for all tests. The distance covered in the tests was 57% (1098 ± 680 vs. 700 ± 272 m), 119% (2325 ± 778 vs. 1062 ± 285 m) and 238% (1743 ± 460 vs. 515 ± 113 m) higher (p ≤ .016), respectively for football-trained than for non-sports active boys aged 9-11, 12-13 and 14-16 years. The typical errors of measurement for Yo-Yo distance, expressed as a percentage of the coefficient of variation (confidence interval), were 11.1% (9.0-14.7%), 10.1% (8.1-13.7%) and 8.5% (6.7-11.7%) for football players aged 9-11, 12-13 and 14-16 years, respectively, with corresponding values of 9.3% (7.4-12.8%), 10.2% (8.1-14.0%) and 8.5% (6.8-11.3%) for non-sports active boys. Intraclass correlation coefficient values for test-retest were excellent in both groups (range: 0.844-0.981). Relative HR peak did not differ significantly between the groups in test and retest. In conclusion, Yo-Yo intermittent test performances and HR peak are reliable for 9- to 16-year-old footballers and non-sports active boys. Additionally, performances of the three Yo-Yo tests were seemingly better for football-trained than for non-sports active boys, providing evidence of construct validity.